ENHANCEMENT OF ANTIMICROORGANISM ACTIVITY AND DEGRADABILITY OF PICKLE SKIN BY MODIFICATION WITH NANOPARTICLE PRODUCED FROM RED ALGAE (Gracilaria sp.) - Rohaeti, Eli; Ramadhani, Zahra Fauzia; Ikhsan, Jaslin; Laksono, Endang Widjajanti; Lestari, Dewi Yuanita (CENTRAL ASIA AND THE CAUCASUS, 2022)
The objectives of this research were to characterize nanoparticles prepared with three methods, i.e. extraction, microwave, and ultrasound, and also to study the effect of nanoparticles in modification of pickle skin on hydrophobicity properties, mechanical properties, antimicrobial activity, and biodegradation of skin. A silver nanoparticle was prepared by using an extract of red algae to change silver ion to nano. Extract solution of red algae was produced by using water solvent and then the mixture of extract and nitrate silver solution was shaken for 24 hours in extraction method. The mixture was treated in microwave for 4 min at a power of 300 W to complete the formation of nano. In the ultrasound method, the mixture was ultrasound treatment for 30 min. Characterization was performed using a UV-VIS spectrophotometer and a particle size analyzer to analyze silver nanoparticles, and also an Atomic Absorption Spectrophotometer to determine content of silver in laundry waste of pickle goat skin. Characterization of modified pickle skin was conducted by determining hydrophobicity,mechanical properties, antibacterial and antifungal activity against Escherichia coli, Staphylococcus epidermidis, and Candida albicans, and also biodegradability of a pickle. Based on the results of UV-VIS and PSA analysis, silver nanoparticles were identified at a wavelength of 416.5 nm with a particle size of 77.2 nm for the microwave method, a wavelength of 421.0 nm with a particle size of 90.4 nm for the extraction method, and a wavelength of 436.5 nm with a particle size of 73.0 nm for the ultrasound method. There were significant differences in the hydrophobicity, mechanical properties, activities of anti-bacteria and anti-fungi, and also degradability of pickle skin.